Evaluation of Nutritional Quality of Under-utilized Wild Yams of Western Ghats of India - Irfa, Anwar; M. N., Sheela; Athira, Jyothy; K. I., Asha; S., Shanavas; P. V., Abhilash (JOURNAL OF ROOT CROPS, 2019)
Wild Yams belonging to the family Dioscoreaceae makes significant contribution in the diets of the tribals in India. Wild yams are considered as a â€œlife savingâ€ crop among many tribal community. They also have immense medicinal properties due to the presence of secondary metabolites especially diosgenin. In this study, biochemical variation among the major wild yams were studied to identify nutrient dense genotypes in germplasm. The biochemical evaluation of starch, sugar, crude protein, crude fat and crude fibre was carried out keeping in mind the nutritive value of the yam tubers. The result indicated that wild yams have abundant nutrient richness than the cultivated greater yam varieties. Among the Dioscorea species, D. oppositifolia, one of the most common wild yams in India, had the highest starch content (28.90%). D. floribunda had the highest content of sugar (1.75%), fibre (0.40%) and fat (8.05%). D. bulbifera had the highest protein content (4.23%) in fresh tuber. From the genetic correlations estimated, the fibre content showed negative correlation to starch content (-0.1956).